2017
DOI: 10.1371/journal.pone.0169864
|View full text |Cite
|
Sign up to set email alerts
|

A MRI-Compatible Combined Mechanical Loading and MR Elastography Setup to Study Deformation-Induced Skeletal Muscle Damage in Rats

Abstract: Deformation of skeletal muscle in the proximity of bony structures may lead to deep tissue injury category of pressure ulcers. Changes in mechanical properties have been proposed as a risk factor in the development of deep tissue injury and may be useful as a diagnostic tool for early detection. MRE allows for the estimation of mechanical properties of soft tissue through analysis of shear wave data. The shear waves originate from vibrations induced by an external actuator placed on the tissue surface. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 89 publications
3
28
0
Order By: Relevance
“…MRE revealed a local hotspot of elevated G d , G l , and |G*|near the center of deformation directly after load release at Day 0, whereas T 2 was elevated in a much larger area. This difference in spatial extend can be explained by higher specificity of T 2 for fluid accumulation, which diffuses proximally and distally along the muscle fibers after injury . Similar to our results, Lv et al found elevated shear stiffness in skeletal muscle of rabbits up to 72 hours after crush injury with ultrasound elastography, which was attributed to swollen muscle cells and increased interstitial space .…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…MRE revealed a local hotspot of elevated G d , G l , and |G*|near the center of deformation directly after load release at Day 0, whereas T 2 was elevated in a much larger area. This difference in spatial extend can be explained by higher specificity of T 2 for fluid accumulation, which diffuses proximally and distally along the muscle fibers after injury . Similar to our results, Lv et al found elevated shear stiffness in skeletal muscle of rabbits up to 72 hours after crush injury with ultrasound elastography, which was attributed to swollen muscle cells and increased interstitial space .…”
Section: Discussionsupporting
confidence: 66%
“…The T 2 ‐weighted and T 2 ‐mapping measurements were also performed during the period of deformation. The rat was placed in supine position in the MR compatible indentation and MRE setup and anesthetized with isoflurane (4.0 vol.% for induction, 1.0–2.0 vol.% for maintenance) in 0.6 L/min medical air . To review briefly, the setup consisted of an indentation and MRE part (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations